Translation Technique Analysis of Dark Jokes In The Subtitle of Joker Movie 2019 - Irfan Azis (Green Publisher Indonesia, 2024)
The study focuses on analyzing the translation technique of dark jokes in the subtitle of Joker movie 2019 that classified as a qualitative descriptive study. The Source of data that the user is taken from the original subtitle of the movie. This study formulated two research questions concerning the form of dark jokes and translation technique in the subtitle of dark jokes. This study applied the theory of Molina and Albir (2002) to analyze the translation technique. The result of this study finds two forms of dark jokes which are dialogue and monologue. Both of form has 6 data of the study. Then, the study found 7 translation techniques that were used in translating dark jokes of the Joker movie 2019 subtitle. Those are adaptation, borrowing, Linguistic Amplification, Linguistic compression, Literal Translation, Modulation, and Reduction. Translation techniques used were 7 linguistic compressions, 7 literal translation, 3 adaptation, 2 borrowings, 2 modulations, 1 linguistic amplification, 1 reduction. Linguistic compression and literal translation are a most applied technique that used in dark jokes of joker movie subtitle.